KONSEP DASAR EVALUASI DALAM KURIKULUM BERBASIS KKNI - KASMAH Kasmah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract: The curriculum is an educational design that encompasses all student experiences in colleges. KKNI is a framework of competency qualification that can match, equalize and integrate between the field of education and the field of job training and work experience in the framework of giving the recognition of work competence in accordance with the structure of work in various sectors. Curriculum changes affect the concept of evaluation, curriculum changes give color in the implementation of the curriculum. The principles of learning evaluation in the KKNI-based curriculum include: educative, authentic, objective, accountable, and transparent principles that are conducted in an integrated manner. The assessment technique consists of observation, participation, performance, written test, oral test, and questionnaire. The assessment instrument consists of process assessment in the form of rubric and / or result assessment in the form of portfolio or design work. The assessment mechanism in the KKNI-based curriculum consists of (a) preparing, submitting, agreeing on the stages, techniques, instruments, criteria, indicators, and assessment weights between the assessors and those assessed in accordance with the lesson plans; (b) carry out the appraisal process in accordance with the stages, techniques, instruments, criteria, indicators and weights of assessment that contain the assessment principles as referred to in Article 20; (c) provide feedback and opportunities to confirm students’ assessment results; and (d) documenting assessments of process and student learning outcomes in an accountable and transparent manner. Implementation of the assessment consists of the planning stage, task assignment activities or questions, performance observation, return of observation sheet, and the final value. Reporting of the results of the assessment in the form of qualification of student success in taking a course expressed in the range: letter A is equivalent to number 4; letter B is equivalent to number 3; letter C is equivalent to number 2; the letter D is equivalent to the number 1 categorized less; or the letter E is. Keywords: Basic concept of evaluation, curriculum based on Indonesia National Qualification Framework